Urban outcasts: A camparative sociology of advanced marginality - Wacquant, Loic (Cambridge Polity Press, 2008)
Breaking with the exoticizing cast of public discourse and conventional research, Urban Outcasts takes the reader inside the black ghetto of Chicago and the deindustrializing banlieue of Paris to discover that urban marginality is not everywhere the same. Drawing on a wealth of original field, survey and historical data, Loïc Wacquant shows that the involution of America's urban core after the 1960s is due not to the emergence of an 'underclass', but to the joint withdrawal of market and state fostered by public policies of racial separation and urban abandonment. In European cities, by contrast, the spread of districts of 'exclusion' does not herald the formation of ghettos.